High-Voltage Converter for the Traction Application. (29th June 2016) - Volskiy, Sergey; Skorokhod, Yury; Sorokin, Dmitriy
Abstract : High-voltage converter employing IGCT switches (V D C = 2800  V) for traction application is presented. Such a power traction drive operates with an unstable input voltage over2000 ⋯ 4000  V DC and with an output power up to 1200 kW. The original power circuit of the high-voltage converter is demonstrated. Development of the attractive approach to designing the low-loss snubber circuits of the high-frequency IGCT switches is proposed. It is established on the complex multilevel analysis of the transient phenomena and power losses. The essential characteristics of the critical parameters under transient modes and the relation between the snubber circuit parameters and the losses are discussed. Experimental results for the prototype demonstrate the properties of new power circuit. The test results confirm the proposed high-voltage converter performance capability as well as verifying the suitability of the conception for its use in the Russian suburban train power system and other high-voltage applications.